(untitled) (Journal of economic and management development research, 2025)
Under the wave of global digital economy, digital transformation has become an inevitable choice for traditional enterprises to seek survival and development, but its process is full of challenges, and a single element cannot fully explain the complex mechanism of successful transformation. Therefore, this paper takes the dynamic capability theory as the analysis framework and adopts the qualitative comparative analysis method to carry out the dynamic analysis and comparison of two typical traditional enterprises. The study concludes that the success of enterprise digital transformation does not rely on an isolated dynamic capability, but on the existence of diversified effective capability configurations, which correspond to different transformation paths, such as "capability restructuring-led" and "opportunity capture-driven" paths, reflecting the characteristics of different paths to the same destination. This study not only expands the application of dynamic capability theory in digital contexts through the perspective of converged configuration but also provides important practical enlightenment for traditional enterprises to choose the transformation path based on their own conditions.